Thinking About God Encourages Prosociality Toward Religious Outgroups: A Cross-Cultural Investigation. (June 2023) - Pasek, Michael H.; Kelly, John Michael; Shackleford, Crystal; White, Cindel J. M.; Vishkin, Allon; Smith, Julia M.; Norenzayan, Ara; Shariff, Azim; Ginges, Jeremy
Most humans believe in a god or gods, a belief that may promote prosociality toward coreligionists. A critical question is whether such enhanced prosociality is primarily parochial and confined to the religious ingroup or whether it extends to members of religious outgroups. To address this question, we conducted field and online experiments with Christian, Muslim, Hindu, and Jewish adults in the Middle East, Fiji, and the United States ( N = 4, 753). Participants were given the opportunity to share money with anonymous strangers from different ethno-religious groups. We manipulated whether they were asked to think about their god before making their choice. Thinking about God increased giving by 11% (4.17% of the total stake), an increase that was extended equally to ingroup and outgroup members. This suggests that belief in a god or gods may facilitate intergroup cooperation, particularly in economic transactions, even in contexts with heightened intergroup tension.